Adoption and Impact of Green Manufacturing Practices on Sustainable Industrial Development in Anambra State, Nigeria - Charles Onyeka Nwamekwe; Igbokwe Nkemakonam Chidiebube; Ono Chukwuma Godfrey; Nwabunwanne Emeka Celestine; Aguh Patrick Sunday (Journal Majelis Paspama, 2025)
This study examines the adoption and impact of green manufacturing practices on sustainable industrial development in Anambra State, Nigeria. Focusing on major industrial hubs such as Nnewi, Onitsha, and Awka, the research explores how local industries integrate sustainable production strategies, including renewable energy use, lean production, waste reduction, and eco-friendly material adoption, within a context of environmental, economic, and social challenges. Findings reveal that while large firms have made notable progress, installing solar systems, improving process efficiency, and complying with export-driven eco-standards, small and medium-sized enterprises (SMEs) face significant barriers, including high capital costs, limited technical expertise, outdated machinery, and weak policy enforcement. Despite these challenges, the study demonstrates that green practices yield substantial benefits: reducing greenhouse gas emissions and material waste by up to 15–20%, lowering energy costs, enabling access to green product markets, and fostering new employment opportunities in waste management, renewable energy, and environmental consulting. The paper underscores the pivotal role of industrial engineers in driving eco-efficiency through lean-green integration and digital tools, while highlighting the need for robust policy frameworks, financial incentives, and capacity-building initiatives. Ultimately, the research positions Anambra State as a potential model for sustainable industrial growth in Nigeria, aligning with the United Nations Sustainable Development Goals (SDGs) and national climate commitments under the Paris Agreement.